Impact of physical treatments on stability and radical scavenging capacity of anthocyanidins - Sivamaruthi B. (2017)
© 2016 The Authors. Published by Innovare Academic Sciences Pvt Ltd. Objective: The aim of the study was to evaluate the chemical stability and antioxidant ability of selected anthocyanidin (ACN) upon various commonly used physical treatments. Methods: Pure compounds of representative ACNs (cyanidin, peonidin) were subjected to microwave, heat, and sonication treatments followed by analyzing the rate of degradation by LC-MS. The changes in the antioxidant ability of ACNs were also assessed by DPPH and ABTS assay. Results: All the tested treatment strategies accelerated the degradation and diminished the antioxidant capacity of pure ACN, more specifically heat exposure cause ~ 90% of degradation and ∼3 fold reduction in antioxidant capacity. About 91.34% and 87.73% of cyanidin and peonidin degradation were documented after heat treatment, respectively. Relatively sonication has not accelerated the ACN debasement, but significant level of degradation (p < 0.05) was observed. Conclusion: The study results suggested that the maximum concern is required for the selection of the method of the degerming process during the production of precious formulations. This study revealed that microwave and sonication processes are better than dry heat based aseptic methods for pure ACNs based product, especially in pharmaceuticals with respect to the stability and bioactivity of ACN.